(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Today availability of e-resourcesin a university library is very common. But the proper and maximum use is a matter for discussion. Many researchstudies have focused on how people use electronic resources or on theirfeelings about electronic and print resources in the library in the lastseveral years. These usage studies drawmany conclusions about the behavior and preferences of library users, althoughsometimes the conclusions are contradictory or unclear. This studies use avariety of research methods, including observation, surveys, interviews,experiments and transaction log analysis. Some surveys or interviews ask questions about preference, including howusers feel about the library or about specific media; others ask questions thatprovide information on user behavior. Observations, experiments, and logs also show what users do, but do notalways reveal preferences or motivations. Each of these methods allows different types of conclusions and it isonly when they are taken together that we can get a full picture of what usersactually do, what they would prefer andwhat they are likely to do in the future. The findings confirm the importanceof e-resources to partner institutions, as they are used daily by staff in allareas of their work. We also found thatthere are many areas of good practice and innovative use of these resources foradministrative, marketing and teaching and learning purposed. There is also a considerable amount ofresearch based on the use of e-resources, particularly in the specialistcolleges. Most institutions have eithera formalized e-learning leader; or all institutions offer staff training in thisarea. There are two areas of e-resourceuse that are particularly well developed; firstly the use of social networkingsites (Facebook and Twitter) as well as the Youtube website, e.g. for marketingand as a learning and teaching aid.